2010
DOI: 10.1016/j.diabet.2010.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Continuous glucose monitoring reduces both hypoglycaemia and HbA1c in hypoglycaemia-prone type 1 diabetic patients treated with a portable pump

Abstract: Aim. -This study aimed to assess the effectiveness of continuous glucose monitoring (CGM) for glucose control in type 1 diabetic patients treated by continuous subcutaneous insulin infusion (CSII) and presenting with frequent hypoglycaemic episodes.Methods. -Thirteen patients with type 1 diabetes (diabetes duration: 25 ± 15 years; CSII duration: 5.5 ± 7.0 years), with more than six recorded capillary blood glucose (CBG) values < 60 mg/dL, according to their metres for the past 14 days, were offered the permane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…58 Another study reported improvement on the Physical Component Score of the Short Form-12 favoring rt-CGM, but no difference was seen between the comparison arms on the Mental Component Score at 26 weeks (low strength of evidence). 65 No difference was found in the effects on diabetes-related quality of life in either of 2 studies comparing rt-CGM and SMBG (low strength of evidence), 57,65 while 1 study that reported effect on quality of life related to diabetes treatment demonstrated less fear of hypoglycemia with rt-CGM than with SMBG (insufficient strength of evidence). 65 None of the studies evaluated the comparative effectiveness of rt-CGM versus SMBG in terms of mortality, microvascular or macrovascular disease, weight, or any other process measure.…”
Section: Pregnant Women With Pre-existing T1dmmentioning
confidence: 99%
See 2 more Smart Citations
“…58 Another study reported improvement on the Physical Component Score of the Short Form-12 favoring rt-CGM, but no difference was seen between the comparison arms on the Mental Component Score at 26 weeks (low strength of evidence). 65 No difference was found in the effects on diabetes-related quality of life in either of 2 studies comparing rt-CGM and SMBG (low strength of evidence), 57,65 while 1 study that reported effect on quality of life related to diabetes treatment demonstrated less fear of hypoglycemia with rt-CGM than with SMBG (insufficient strength of evidence). 65 None of the studies evaluated the comparative effectiveness of rt-CGM versus SMBG in terms of mortality, microvascular or macrovascular disease, weight, or any other process measure.…”
Section: Pregnant Women With Pre-existing T1dmmentioning
confidence: 99%
“…23,[57][58][59][60][61][62][63][64][65] The median follow-up time for all studies was 24 weeks, and median enrollment of 132 patients was reported in 6 studies. The mean age of participants was 24 years in the rt-CGM group and 25 years in the SMBG group, with mean baseline A1c of 8.3% in both groups.…”
Section: ■■ Comparative Effectiveness Of Rt-cgm Versus Smbgmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17][18][19][20][21][22][23][24][25][26] The primary goal of most clinical studies of RT-CGM conducted to date has been to demonstrate that the technology significantly reduces HbA1c even though these devices also should decrease the risk of hypoglycemia, which is a major barrier to patients achieving glycemic targets. 27 Although several studies have shown that use of RT-CGM significantly reduces time spent in hypoglycemia in T1DM patients, 14,16,28 initial RCTs evaluating RT-CGM were not designed or adequately powered to determine the efficacy of RT-CGM for reducing the frequency of hypoglycemic events in general and severe hypoglycemic events in particular.…”
Section: Evidence For Reducing Hypoglycemia Eventsmentioning
confidence: 99%
“…A study having as its principal objective the reduction of mild hypoglycaemias [35] demonstrates that the use of a CGM device for six months by patients with well-controlled type 1 diabetes (HbA 1c < 7.5%) treated by pump (the majority) or multiple injections makes possible a reduction by half of the time spent in hypoglycaemia (P = 0.03) and a supplementary improvement of HbA 1c (-0.27%, P = 0.0008) [35]. Another study recruited a small number of patients on the basis of frequency of hypoglycaemia (more than 6 episodes < 60 mg/ dl in the last 15 days) and showed a 50% reduction in the frequency of hypoglycaemias and a simultaneous reduction in HbA 1c when a CGM device as opposed to SBMG is used for three months [36].…”
Section: Hypoglycaemia and Glucose Variabilitymentioning
confidence: 99%